The Learning Styles of Pre-service Teachers - Fernández, Erika; Narváez, Oscar (CIEX JOURNAL, 2021)
The main aims of this research are to highlight the importance of identifying what learning styles are being used by undergraduate English students in a teacher training program and describe how they combine their learning strategies with the learning styles. This study used a mixed method research design to make an exploratory and explanatory description of students’ learning styles. Data were collected using two instruments: The VARK questionnaire and an unstructured interview. The study took place in a public School of Languages at a University in Veracruz. The total sample included 69 beginner English students who filled the VARK questionnaire. To collect qualitative data, four beginner English students participated in an individual interview. The findings revealed that students use multimodal learning styles to learn a second language, and that participants use sustainable strategies with their learning style preference.